Klebsiella pneumoniae AcrAB Efflux Pump Contributes to Antimicrobial Resistance and Virulence - Padilla, Emma (American Society for Microbiology (ASM), 2010)
Respiratory infections caused by Klebsiella pneumoniae are characterized by high rates of mortality and morbidity. Management of these infections is often difficult, due to the high frequency of strains that are resistant to multiple antimicrobial agents. Multidrug efflux pumps play a major role as a mechanism of antimicrobial resistance in Gram-negative pathogens. In the present study, we investigated the role of the K. pneumoniae AcrRAB operon in antimicrobial resistance and virulence by using isogenic knockouts deficient in the AcrB component and the AcrR repressor, both derived from the virulent strain 52145R. We demonstrated that the AcrB knockout was more susceptible, not only to quinolones, but also to other antimicrobial agents, including β-lactams, than the wild-type strain and the AcrR knockout. We further showed that the AcrB knockout was more susceptible to antimicrobial agents present in human bronchoalveolar lavage fluid and to human antimicrobial peptides than the wild-type strain and the AcrR knockout. Finally, the AcrB knockout exhibited a reduced capacity to cause pneumonia in a murine model, in contrast to the wild-type strain. The results of this study suggest that, in addition to contributing to the multidrug resistance phenotype, the AcrAB efflux pump may represent a novel virulence factor required for K. pneumoniae to resist innate immune defense mechanisms of the lung, thus facilitating the onset of pneumonia.